Bowel Obstruction and Ventral Hernia After Laparoscopic Versus Open Surgery for Rectal Cancer in A Randomized Trial (COLOR II). Issue 1 (January 2019) - Petersson, Josefin; Koedam, Thomas W.; Bonjer, H. Jaap; Andersson, John; Angenete, Eva; Bock, David; Cuesta, Miguel A.; Deijen, Charlotte L.; Fürst, Alois; Lacy, Antonio M.; Rosenberg, Jacob; Haglind, Eva
Abstract : Objective: The aim of this study was to evaluate the risk of bowel obstruction, incisional, and parastomal hernia following laparoscopic versus open surgery for rectal cancer. Summary Background Data: Laparoscopic surgery for rectal cancer has been adopted worldwide, after trials reported similar oncological outcomes compared with open surgery. Little is known about long-term morbidity, including bowel obstruction, incisional, and parastomal hernia following surgery. Methods: Patients included in the international, multicenter, noninferior, open-label, randomized COLOR II trial were followed for five years. Primary endpoint was local recurrence at 3-year follow-up. Secondary endpoints included bowel obstruction, incisional and parastomal hernia within 5 years, and the current article reports on these secondary endpoints. Results: All 1044 patients included in the COLOR II trial were analyzed. There was no difference in risk of bowel obstruction, incisional, or parastomal hernia following laparoscopic or open surgery for rectal cancer. Conclusion: Based on long-term morbidity outcomes, laparoscopic surgery for rectal cancer could be considered a routine technique as there are no differences with open surgery.